Alzheimer’s Disease is Associated with Increased Risk of Osteoporosis: The Chongqing Aging Study - Liu, Dong; Zhou, Huadong; Tao, Yong; Tan, Jun; Chen, Lin; Huang, Haiyang; Chen, Yang; Li, Yafei; Zhou, Rui (Current Alzheimer Research, 2016)
Objective: The aim of this study was to analyze the relationship between Alzheimer’s disease (AD) and a risk of osteoporosis in the elderly cohort of Chongqing, China. Methods: A prospective study with 6 years of follow-up in 1802 patients aged 60– 75 was conducted from January 2007 to June 2013. Dual energy X-ray absorptiometry was utilized to evaluate bone mineral density (BMD). Their cognitive function was detected using the Chinese version of the Mini-Mental State Examination (MMSE) and a detection of the instrumental activities of daily living (ADL). Cox proportional hazards models were used to detect the association between AD and the risk of osteoporosis. Results: After adjusting for age, female, AD, 25-hydroxyvitamine D (25(OH)D), smoking, drinking and stroke, AD (Hazard ratio, HR 2.48, 95%CI 1.66-2.94), age (HR 1.36, 95% CI 1.14-1.60), female (HR 1.39, 95% CI 1.17-1.65), 25(OH)D (HR1.34, 95%CI 1.11-1.59), current smoking (HR 1.27, 95%CI 1.22-1.43), daily drinking (HR 1.33, 95%CI 1.11-1.52) and stroke (HR 1.26, 95%CI 1.14-1.58) were associated with increased risk of osteoporosis. In osteoporosis fracture group, osteoporosis with AD was more common than osteoporosis with normal cognition function. Conclusion: AD was associated with an increased risk of osteoporosis in the elderly cohort of Chongqing, China.
Keywords: estrogen